Simulation of deposit growth onto recuperator tubes in pit furnaces. - WACŁAWIAK, Krzysztof (Engineering Transactions, 2016)
Nowadays, the operation of pit furnaces without air preheating is not acceptable. However, a deposit growth on the tubes of air preheaters significantly decreases their efficiency. This paper presents a two-dimensional simulation of the phenomenon of deposition on the tubes of air preheaters with a staggered tube layout. It has been shown that it is possible to predict the deposit shape and its effect on heat transfer from combustion gas to combustion air.